Application of dural suturing in the endoscopic endonasal approach to the sellar region - Liu, Zhiyuan; Zhao, Liang; Wang, Yu; Dai, Kexiang; Lu, Ailin; Zhao, Peng (Frontiers in Surgery, 2022)
Objectives: The endoscopic endonasal approach (EEA) is widely used in the treatment of cranial base tumors. Skull base reconstruction is an crucial part of EEA, which has a great impact on patients’ prognosis. In this study, we report our experience with sellar dural suturing in cranial base reconstruction and retrospectively analyze its effect. Methods: The clinical data of 134 patients who underwent EEA surgery and suffered intraoperative CSF leakage in the Department of Neurosurgery of the First Affiliated Hospital of Nanjing Medical University, from October 2018 to November 2020 were retrospectively collected and analyzed. According to whether sellar dural suturing was performed during the operation, they were divided into the suture group (55 cases) and control group (79 cases). Results: The results showed that dural suturing of the sellar floor effectively reduced the postoperative hospitalization duration (P = 0.026) and the use rates of lumbar drainage (P = 0.047), autologous fat transplantation (P = 0.038) and pedicled nasoseptal flaps (P = 0.026). Conclusion: Sellar dural suturing under endoscopy is a promising and effective method for cranial base reconstruction in EEA surgery and is worthy of clinical application.